GAMBARAN POLA KONSUMSI ANAK STUNTING DI SDN 064994 KELURAHAN TANAH ENAM RATUS KECAMATAN MEDAN MARELAN - Lisda Oktari; Ernawati Nasution; Fitri Ardiani (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
The children who experience obstacles into growth caused lack of the adequate food intake and infectious diseases, so that exacerbate malnutrition of children. This condition more difficult to cope growth disorders that finally likely occurrence of stunted. This research aims to know description the consumption pattern of child stunting in SDN 064994 Medan Marelan. Types of study is an observational of cross sectional study design. This study doing by calculating energy sufficiency, protein, calcium, phosphorus, magnesium, zinc, vitamin A and vitamin C by using 24 hours food recall method. This sample of research is all students stunting as many as 67 people. The results of this study to show that the consumption pattern of child stunting in SDN 064994 according to the amount of food based on the adequacy of macro nutrients such as energy sufficiency is 68,7% deficient category, protein sufficiency is 47,8% good category, and to the adequacy of micro nutrients such as calcium sufficiency is 80,6%, phosphorus is 53,7%, zinc is 98,5% and vitamin C is 80,6% medium category, while magnesium is 62,7% and vitamin A is 50,7% sufficient category. By the type of food consumed an average of 3 types per day and most of the child stunting consume rice as staple food, fish and eggs as a side dish, spinach, kale and mustard greens as a vegetable. From the results of the study suggested the school in cooperate with the primary health care that gives nutritional education school children and to cafeteria that provide healthy snacks and to students stunting to consume vegetables and fruits every day to be able to catch up growth. Keywords : Consumption Pattern, Stunting, Elementary School